Integrative Analysis of the Geothermal Structure in Kepahiang: Insights from Magnetotelluric, Gravity, and Remote Sensing Techniques - Nindia E. Larasati; Agus Laesanpura; Asep Sugianto (Postgraduate, University of Mataram, 2023)
This research was conducted to determine the structure and depth of the reservoir using remote sensing as an initial survey to assess the geological alignment direction, employing ALOS PALSAR radar imagery. Subsequently, further surveys were conducted using the magnetotelluric and gravity methods to analyze the structure and depth of the geothermal reservoir. The magnetotelluric data were processed using Phoenix software, where the data was transformed from the time domain to the frequency domain using Fourier transformation, and processed to obtain apparent resistivity and phase. The MT data was integrated with gravity data, and the gravity data underwent standard correction procedures to obtain the Complete Bouguer Anomaly (CBA) map. Two-dimensional (2D) inversion using the NLCG algorithm and 2D forward modeling of the gravity data were performed. The dominant alignment pattern obtained was northwest-southeast, with an orientation of 320Â° NW or 140Â° SE. Based on the results of geological alignment, a profile is produced that is perpendicular to the straightness. The results from the 2D inversion and gravity forward modeling indicated that the geothermal reservoir is likely located beneath the caprock at an estimated depth of approximately 1800 m, with resistivity values ranging from 32 to 256 Ohm-m and a density value is 2.6 gr/cc.